Enhancing Scientific Literacy on Earth and Solar System Concepts Through the Reading to Learn (R2L) Model: A Classroom Action Research Study - Hakiim, Luqmanul; Herunata, Herunata; Asih, Agustuti Hasto Welas; Gufron, Gufron; Rokhim, Deni Ainur; Yenadiputri, Eukharistia; Smith, Diana Novel (Orbital: The Electronic Journal of Chemistry, 2025)
Indonesia’s low science literacy, as reflected by its 70th place ranking out of 78 countries in the 2018 PISA rankings, highlights the need for better education strategies. This research aims to examine the application of the R2L (Reading to Learn) model to increase scientific literacy. Using a Collaborative Classroom Action Research design (Kemmis and Taggart model), the study was conducted over two cycles with 36 students from class VII-8 at SMP Negeri 3 Candi. Data collected included students’ scientific literacy, learning implementation, reflection, and responses through written tests, observation, and questionnaires. Learning implementation quality also increased from 92.01% to 97.57%, with student responses averaging 83.61%, indicating high engagement. Thus, this research confirms that the R2L model effectively improves scientific literacy of class VII students at SMP Negeri 3 Candi in science learning.